Co-Branding Citra Pertanian dan Daya Tarik Agrowisata: Studi Komparasi Taiwan dan Indonesia - Nurina Rachmita; Raldi Hendro Koestoer (JURNAL MASTER PARIWISATA, 2021)
Indonesia is an agrarian country having rich in variety of natural and biological resources. With such capacity, Indonesia has a chance to develop agribusiness, as for in the area of agritourism. However, the problem is the farmers have a limitation to create agricultural activities for tourism. This study explains agritourism development in Indonesia with Taiwan agritourism-oriented. The method uses combine approach, i.e., literature and comparative studies, and analyze them with relevant theories. The result of this study found that agritourism management in Indonesia is still limited and has not been optimized. The conclusion of this study is that Taiwan case study can be applied to promote agritourism as for Indonesia, not even limited to the agriculture sector, but it can also be applied to the cultural sector. Keywords: Agritourism, agriculture activities, tourism, marketing strategy, farm tourism